(untitled) (Advancements in Homeopathic Research, 2024)
Soon after discovery of Ptelea trifoliata in colonial America, this attractive aromatic shrub became popular in Old World botanical gardens. First medical indications as anthelmintic and vulnerary, by Schoepf in 1787, were extended in nineteenth century homoeopathic literature to include alleged usefulness as a febrifuge, tonic, and in treatment of numerous chronic conditions. Presence of berberine, or other substances reported by early workers, has not been confirmed.